IMPROVING THE INNOVATIVE BEHAVIOR OF VOCATIONAL HIGH SCHOOL ENGLISH TEACHERS THROUGH THE USE OF SCRATCH - Tri Astuti, Natalia; Frijuniarsi, Nurul (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2025)
This community engagement activity aimed to enhance the innovative behavior of vocational high school English teachers in Depok City, specifically through the utilization of SCRATCH. The primary objective was to make learning more engaging, enjoyable, and relevant to contemporary educational needs. This improvement is crucial for teachers to develop interactive and highly beneficial learning materials, thereby optimizing learning outcomes. Information regarding the partners' needs and challenges was gathered using survey techniques, observation, and interviews. The activity was conducted over a single day for six hours. The implementation team provided direct guidance and support on the effective use of SCRATCH. The session began with an introduction to the SCRATCH application and an exploration of the fundamentals of visual programming, with the goal of enabling participants to create interactive projects. Subsequently, the tangible output of this activity was the development of simple yet interactive learning media by the participating teachers. The results of this activity were highly satisfactory, as participants acquired new knowledge and skills not only in English learning media but also in foundational visual programming concepts.